Risk stratification for major adverse cardiac events and ventricular tachyarrhythmias by cardiac MRI in patients with cardiac sarcoidosis. Issue 2 (1st August 2016) - Yasuda, Masakazu; Iwanaga, Yoshitaka; Kato, Takao; Izumi, Toshiaki; Inuzuka, Yasutaka; Nakamura, Takashi; Miyaji, Yuki; Kawamura, Takayuki; Ikeguchi, Shigeru; Inoko, Moriaki; Kurita, Takashi; Miyazaki, Shunichi
Abstract : Background: The presence of myocardial fibrosis by cardiac MRI has prognostic value in cardiac sarcoidosis, and localisation may be equally relevant to clinical outcomes. Objective: We aimed to analyse cardiac damage and function in detail and explore the relationship with clinical outcomes in patients with cardiac sarcoidosis using cardiac MRI. Methods: We included 81 consecutive patients with cardiac sarcoidosis undergoing cardiac MR. Left ventricular mass and fibrosis mass were calculated, and localisation was analysed using a 17-segment model. Participants underwent follow-up through 2015, and the development of major adverse cardiac events including ventricular tachyarrhythmias was recorded. Results: Increased left ventricular fibrosis mass was associated with increased prevalence of ventricular tachyarrhythmias (p<0.001). When localisation was defined as the sum of late gadolinium enhancement in the left ventricular basal anterior and basal anteroseptal areas, or the right ventricular area, it was associated with ventricular tachyarrhythmias (p<0.001). Kaplan-Meier analysis during a median follow-up of 22.1 months showed that both the mass and localisation groupings for fibrosis were significantly associated with major adverse cardiac events or ventricular tachyarrhythmias and that when combined, the risk stratification was better than for each variable alone (p<0.001, respectively). By Cox-proportional hazard risk analysis, the localisation grouping was an independent predictor for the both. Conclusions: In patients with cardiac sarcoidosis, both fibrosis mass and its localisation to the basal anterior/anteroseptal left ventricle, or right ventricle was associated with the development of major adverse cardiac events or ventricular tachyarrhythmias. Cardiac MR with late gadolinium enhancement may be useful for improving risk stratification in patients with cardiac sarcoidosis.